English language - Angga Prasetyo Adi; Endriatmo Soetarto; Martua Sihaloho (CV. Literasi Indonesia, 2021)
The resistance of the peasants is inseparable from the social class that is intertwined in it so that this resistance is only a tool of the interests of the actors to secure land. The resistance of Wonogoro farmers in opposing social forestry was due to the redistribution of 2 hectares of land. This study uses a theoretical analysis of class dynamics and agrarian change in rural areas. Seeing the social class of farmers who can mobilize farmers to oppose social forestry based on control over land tenure. This research uses a critical paradigm. The research location is in the Wonogoro area, Malang Regency, East Java, Indonesia. This study used purposive sampling with 20 respondents. The results of the research are the mystification of peasant resistance as shown by the mobilization of proletarian farmers by capital farmers. The mystification of peasants 'resistance shows the disparity of the peasants' social class with land management. Unbalanced land management is due to massive privatization. Unequal land tenure forms the social class of farmers. The capital peasant class by controlling the land can control the proletarian peasants as agricultural laborers. The resistance of farmers against social forestry shows that there is the mobilization of resistance by capital farmers to secure land with a 2-hectare land redistribution scheme.